Identifikasi Karakteristik Mineral Magnetik Berdasarkan Analisis XRF di Lahan Pertanian Sekitar Sungai Biyonga Kabupaten Gorontalo - Gani, Sintia N.; Yunginger, Raghel; Tamuntuan, Gerald H; Demulawa, Meilan (Jurnal Natural Scientiae, 2023)
An analysis of soil chemical elements using X-Ray Fluorescence (XRF) has been conducted on paddy fields in Dutulanaa Village, Gorontalo Regency, and corn farms in Polohungo Village, Gorontalo Regency. Soil samples were taken at three locations, namely corn location 1 (location I), corn location 2 (location II), and paddy fields (location III). At each location, samples were taken at 2 points to obtain 6 pieces. The distance between sampling points is 10 m. Based on the results of XRF measurements, the elements that dominate in paddy fields and corn include silica (Si), iron (Fe), aluminum (Al), calcium (Ca), titanium (Ti), potassium (K), and manganese (Mn), where Si is a diamagnetic element, Fe is a ferromagnetic element, and Al, Ca, Ti, and K are paramagnetic elements. The most significant percentage is silica (Si), 60.27% in corn soil 2 points J2T2. The next highest element is iron (Fe), 29.47% in corn soil, 1 point J1T2. The next element is aluminum (Al), 9.10% in corn soil at 1 point J1T1, calcium (Ca) in corn soil at 2 points J2T2 is 10.03 %, titanium (Ti) was 2.31% in paddy fields at ST5 point and potassium (K) was 2.31% in a paddy field at ST5 point, and the lowest value was manganese (Mn) of 0.59% in corn soil 2 points J2T1. Even some heavy metal elements, such as lead (Pb), were found—zinc (Zn) and manganese (Mn). The highest heavy metal elements were found in agricultural corn land at 2 J2T2 points, namely lead (Pb) at 158 ppm, zinc (Zn) at 4,555 ppm, and manganese (Mn) at 17,100 ppm, where these results have exceeded the threshold of soil quality standards, resulting in environmental pollution of agricultural land.